2018
DOI: 10.1002/adfm.201805157
|View full text |Cite
|
Sign up to set email alerts
|

Protein‐Sized Dye‐Loaded Polymer Nanoparticles for Free Particle Diffusion in Cytosol

Abstract: How small should nanoparticles be in order to travel freely through the cytosol similar to proteins? Answering this question remains a challenge, because the majority of nanoparticles are relatively large and their size cannot be finely tuned to match that of proteins. Here, poly(methyl methacrylate) copolymers with varied fraction and type of charged groups (carboxylate, sulfonate, and trimethylammonium) are developed, yielding nanoparticles with controlled sizes from 50 to 7 nm through nanoprecipitation. Loa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
84
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 49 publications
(94 citation statements)
references
References 85 publications
10
84
0
Order By: Relevance
“…Then, generated cationic R18 dye being adsorbed at the NPs surface could decrease their negative surface charge (Figure ) and, thus, compromise their colloidal stability as observed by DLS. Indeed, we have shown previously that the amount of charged groups on the polymers used for NP formation is crucial for the formation of small particles . The small size of polymer NPs containing R18 with bulky hydrophobic and medium‐sized counterions suggests that these ion pairs probably do not dissociate in water and do not neutralize surface carboxylates.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Then, generated cationic R18 dye being adsorbed at the NPs surface could decrease their negative surface charge (Figure ) and, thus, compromise their colloidal stability as observed by DLS. Indeed, we have shown previously that the amount of charged groups on the polymers used for NP formation is crucial for the formation of small particles . The small size of polymer NPs containing R18 with bulky hydrophobic and medium‐sized counterions suggests that these ion pairs probably do not dissociate in water and do not neutralize surface carboxylates.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, NPs with dispersed dyes (using counterions of medium hydrophobicity, such as B(CF 3 ) 4 and F5‐3PB‐OH), which exhibit stable emission, will be of high interest as robust labels for single molecule/particle tracking and imaging applications. It is well established that brightness, photo‐stability and continuous non‐blinking emission of NPs are of key importance for single‐particle tracking in live cells ,…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The primary approach to improve FRET donor efficiency of a particle together with its light‐harvesting capacity is to minimize its size while keeping the largest possible number of encapsulated donor dyes. Our earlier studies showed that smaller polymer NPs can be obtained by increasing the pH during nanoprecipitation or increasing the charge on the polymer . In the first approach, we performed nanoprecipitation of PMMA‐AspN3‐1.6 % at pH 9, which yielded NPs of 30 nm (Figure S7 A,B).…”
Section: Resultsmentioning
confidence: 98%